Video with multiple representations approach to promote students’ conceptual understanding of intermolecular forces - Erlina Erlina; Eny Enawaty; Husna Amalya Melati; Ira Lestari (Institute of Advanced Engineering and Science, 2023)
A number of studies have reported that the main cause of misconceptions are the abstract concepts and students’ low ability to integrate multiple representations (macroscopic, sub-microscopic and symbolic) in chemistry is also a cause of misconceptions. The aim of this study is to develop the video using multiple representations approach to improve students’ conceptual understanding. The method used is the analyze, design, development, implementation, and evaluation or ADDIE development model. Tests (pre and post) and questionnaire were used to collect the data. A video of intermolecular forces has been developed and tested to 82 first-year cohort students of the Chemistry Education Study Program who had taken basic chemistry courses. The average scores were increased from 57.31 (pre-test) to 78.19 (post-test) with the average gain is 20.88. The statistically significant increase in scores (p=0.000) was found, which signifies that the video could support students’ conceptual understanding. In addition to that, majority of students showed a positive response to the video as 99% (N=82) of them either agree or strongly agree with the statements of the questionnaire. This result verified that the video was successfully maintain students’ attention.